Prinsip Kepemimpinan Dalam Alquran Dan Implementasinya Pada Sosok Rasulullah SAW - Raufan Syiddik Harahap; Zulhimma Zulhimma (Journal of Innovative and Creativity, 2026)
Leadership in Islam encompasses spiritual and moral dimensions derived from the Qur’an and the traditions of Prophet Muhammad SAW. This study aims to examine the principles of leadership in the Qur’an and analyze their implementation in the personality and practices of the Prophet Muhammad SAW as the ideal model of leadership. The research employs a library research method with a qualitative descriptive approach by analyzing Qur’anic verses, hadiths, and both classical and contemporary literature on Islamic leadership. The findings reveal that the Qur’an emphasizes five fundamental principles of leadership: amanah (trust and responsibility), ‘adl (justice), syura (consultation), hikmah (wisdom), and uswah hasanah (exemplary conduct). These principles were practically demonstrated by the Prophet Muhammad SAW throughout his social, political, and religious life. The Prophet exemplified integrity through amanah, upheld justice without discrimination, practiced consultation in decision-making, exercised wisdom in resolving conflicts, and served as a moral exemplar for his followers. The study concludes that the Qur’anic principles of leadership are universal and remain highly relevant in the modern context, providing a framework for leadership that is ethical, just, participatory, and humanistic. This research contributes to the development of an Islamic leadership paradigm capable of addressing global challenges through the integration of moral, ethical, and spiritual values.